Extraction and Purification of Phosphatidic Acid of C18 Fatty Acids from Powdered Soybean Phospholipids - Liu, Daicheng; Tao, Yinhua; Sun, Fazheng; Li, Yunlong (Asian Journal of Chemistry, 2010)
A simple process for efficient extraction of phosphatidic acid from powdered soybean phospholipids is reported. The purity of the extracted phosphatidic acid reached 99 % as analyzed by thin layer chromatography and high-performance liquid chromatography. The fatty acids of the extracted phosphatidic acid were C18 fatty acids (stearic and oleic acids, 43.6 and 56.4 %, respectively) as determined by gas chromatographymass spectrometry. This process may be scaled up for commercial production of high-purity phosphatidic acid.